DnaA protein is not essential for replication of IncFII plasmid NR1. - Tang, X B (1989)
By transformation of dnaA null mutant host cells that are suppressed either by an rnh mutation or by chromosomal integration of a mini-R1 plasmid, it was shown that replication of miniplasmids composed of the NR1 minimal replicon had no absolute dependence upon DnaA protein. In addition, the suppression of the dnaA null mutation by the integrated mini-R1, which is an IncFII relative of NR1, was found to be sensitive to the expression of IncFII-specific plasmid incompatibility. This suggests that the integrative suppression by mini-R1 is under the control of the normal IncFII plasmid replication circuitry. Although NR1 replication had no absolute requirement for DnaA, the copy numbers of NR1-derived miniplasmids were lower in dnaA null mutants, and the plasmids exhibited a much reduced stability of inheritance during subculture in the absence of selection. This suggests that DnaA protein may participate in IncFII plasmid replication in some auxiliary way, such as by increasing the efficiency of formation of an open initiation complex at the plasmid replication origin. Such an auxiliary role for DnaA in IncFII replication would be different from that for replication of most other plasmids examined, for which DnaA has been found to be either essential or unimportant.